Building and sustaining infection prevention and control teams at two pediatric cancer units in Ecuador and Guatemala through a collaboration partnership - Acebo, Joanna J.; Melgar, Mario A.; Homsi, Maysam R.; Gonzalez, Miriam L.; Cojulun, Alicia C.; Antillon-Klussmann, Federico; Eguiguren, Jose M.; Tuomanen, Elaine I.; Caniza, Miguela A. (Frontiers in Oncology, 2025)
BackgroundHospital infection prevention and control (IPC) programs are often insufficient to meet the needs of pediatric oncology units (POUs) in low-resource settings. Accordingly, we established partnerships to build and sustain dedicated IPC teams for two POUs in Ecuador and Guatemala.MethodsEach partnership comprised four phases: (1) planning and preparation; (2) developing the IPC team; (3) sustaining the IPC team; and (4) integrating the IPC team into the institution. The impact of the IPC teams was assessed by monitoring healthcare-associated infections (HAIs) and compliance with IPC practices.ResultsAt Hospital SOLCA–Quito, Ecuador, local champions were identified and trained. These in turn built local IPC teams that led healthcare improvement by using surveillance for outcome measures, monitoring practices for processes measures, and staff training. As the collaboration progressed, infection rates decreased steadily. At SOLCA–Quito, there were 9 HAIs/1000 patient days at baseline in 2010, whereas at the end of 2019, there were 2.6 HAIs/1000 patient days. A similar program was developed at the UNOP hospital in Guatemala, where the HAI rate decreased from 9.9/1000 patient days in 2011 to 5.37/1000 patient days in 2019 and the CLABSI rate decreased from 32.75/1000 catheter days in 2008 to 3.11/1000 catheter days in 2019. Towards the end of the collaborations, the IPC teams were integrated into the institutional structures. The Ecuadorean IPC team was integrated as a link team between the pediatric oncology service and the hospital IPC program. The Guatemalan team became the institutional IPC program staff.ConclusionsOur collaborations decreased HAIs in two POUs. The model proved sustainable and became part of the institutional structures, and it has been replicated in POUs elsewhere.